Guardianship of an Adult of Legal Capacity in Lithuania: Does National Law Comply with Lithuania’s International Obligations? - Krutulytė, Kornelija; Genienė, Rasa (Teisė, 2025)
The article deals with Article 509 of the Code of Civil Procedure of the Republic of Lithuania on guardianship of a person with capacity. Article 509 of the CPC is compared with the possible alternatives to the limitation of legal capacity currently available in the Lithuanian legal system. The guardianship of a person with legal capacity is examined in the context of the United Nations Convention on the Rights of Persons with Disabilities. Article 509 of the CPC is compared with other possible alternatives to the limitation of legal capacity. A brief overview of the types of limitation of legal capacity in Lithuania is given with the current legal regulation of incapacity in the German Federation.
Keywords: care; guardianship; incapacity; legal capacity; limitation of legal capacity; United Nations Convention on the Rights of Persons with Disabilities